Inclusive development of society : proceedings of the 6th International Conference on Management and Technology in Knowledge, Service, Tourism & Hospitality (SERVE 2018), October 6-7 and December 15-16, 2018, Bali, Indonesia, and December 15-16, 2018, Rostov-on-don, Russia - International Conference on Management and Technology in Knowledge, Service, Tourism & Hospitality 2018); Gaol, Ford Lumban (Leiden, The Netherlands : CRC Press/Balkema, 2020)
"Inclusive Development of Society contains papers that were originally presented at the 2018 International Congress on Management and Technology in Knowledge, Service, Tourism & Hospitality (SERVE 2018), held 6-7 October and 15-16 December 2018 in Kuta, Bali, Indonesia and 18-19 October, 2018 at The Southern Federal University, Rostov-on-don, Russia. The contributions deal with various interdisciplinary research topics, particularly in the fields of social sciences, economics and the arts. The papers focus especially on such topics as language, cultural studies, economics, behavior studies, political sciences, media and communication, psychology and human development. The theoretical research studies included here should provide a solid foundation for the development of new tools that explore the possibilities of developing tourism, hospitality, service industries in Knowledge Economic Era, and the empirical papers will advance our knowledge regarding the impact of information technologies in organizations' and institutions' practices. These proceedings should be of interest to academics and professionals in the wider field of social sciences, including disciplines such as education, psychology, tourism and knowledge management"--
OCLC-licensed vendor bibliographic record.
Keywords: Information technology -- Economic aspects -- Congresses; BUSINESS & ECONOMICS / Management Science; BUSINESS & ECONOMICS / Purchasing & Buying; BUSINESS & ECONOMICS / Information Management